HUMAN GROWTH NEW PARADIGM SEBAGAI STRATEGI PENGEMBANGAN SUMBERDAYA MANUSIA (SDM) INDONESIA - Misbahuddin Misbahuddin (Jurnal Aplikasi Manajemen & Kewirausahaan MASSARO, 2019)
This paper is based on two theories that emphasize the paradigm of how the role of education for development. The first is the paradigm of human capital (human capital paradigm), which is influenced by classical economic theory, the Neo Liberal. This theory views and places human resources only as a factor of production. The second is the paradigm that is oriented towards human resource development with the direction of long-term goals, namely human growth paradigm. It is a paradigm that builds HR with an education system that not only relies on intellectual intelligence and psychomotor skills of HR (skills), such as on human capital paradigms but also on personal development that is moral, ethical and independent thanks to the subtlety of sense and silence of conscience conscience (Character).